Seruan Boikot Starbucks: Kampanye Negatif Atau Kampanye Hitam? - Dini Safitri (Jurnal InterAct, 2015)
This study aims to determine the rejection of negative campaigning against Starbucks. A message, “A cup of Starbucks, Worth A drop of blood of Palestine and Lebanon”, circulated from one person to another and then connected to the rest of the world. The message is then denied by the CEO of Starbucks, Howard Schultz, who said that the rumor that Starbucks or Howard provides financial assistance to the government of Israel or the Israeli army is false. But denial is not fully dampening the negative opinion that had already been circulated previously. The method used in this study is a discourse analysis. This study is limited only to explore the case in Indonesia. The unit of analysis is a message in the form of negative campaigning rejection Starbucks, which circulated widely in the community, through a variety of media and community. According to the informant, they are doing it, as a form of solidarity, for the Palestinian people, especially Palestinian children. In addition, they are also trying to find an alternative to other coffee drinks. They tried to turn coffee shops with locally produced coffee. Indonesia is a coffee producing countries, and some regions have their own specialty coffee.